Teaching English from a cultural studies - Rustamova Z.R. (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Culture is learned from the people you interact with as you are socialized. Watching how adults react and talk to new babies is an excellent way to see the actual symbolic transmission of culture among people. People from different cultures would complete the blank in contrasting ways. our specific interest is in the relationship between culture and interpersonal сommunication, we focus on how cultures provide their members with a set of interpretations that they then use as filters to make sense of messages and experiences.